Effects of biochar combined with the application of plant ash and effective microorganisms on the soil in the vegetable facility - Minhan Sun; Shuanxi Fan; Nan Zhang (Scientific Reports)
Abstract In facility agriculture, soil barriers have led to severe soil quality degradation, making it crucial to take effective measures for soil improvement. This research focuses on exploring the impacts of biochar, plant ash, and Effective Microorganisms (EM) on the physical, chemical properties, and nutrient levels of facility-agriculture soil, aiming to find a novel and efficient solution to address the soil-related issues. A field trial was carried out to assess the combined application of biochar, EM bacteria, and plant ash on soil properties. The experiment setup consisted of a blank control (CK) and six treatment groups (T1–T6) with different dosage gradients. The combined application of biochar, plant ash and EM bacteria significantly enhanced various soil properties. Specifically, the pH, soil bulk density, total nitrogen, total phosphorus, total potassium, organic matter, alkaline hydrolyzed nitrogen, available phosphorus, and available potassium levels in facility-agriculture soil increased by 1.1-24.0%, 6.09-9.83%, 32.22-61.26%, 11.82-47.82%, 1.44-6.99%, 19.42-77.23%, 10.64-44.09%, 22.01-49.71%, and 14.11-93.64% respectively. The soil comprehensive fertility index (IFI) showed that this combined application could effectively improve the comprehensive soil fertility, with the T4 treatment (plant ash 3030 kg/hm2 + biochar 6060 kg/hm2 + EM bacteria 37.5:1) demonstrating the best improvement effect. The combined application of biochar, EM bacteria and plant ash can overcome the soil barriers in facility agriculture, mitigate soil acidification and nutrient disorders, promote nutrient supply, and enhance soil fertility. The study provides a practical and innovative approach to relieve the difficulties in facility vegetable cultivation, offering valuable insights for sustainable development in facility agriculture.